2014
DOI: 10.1007/s00403-014-1463-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with low-temperature atmospheric pressure plasma enhances cutaneous delivery of epidermal growth factor by regulating E-cadherin-mediated cell junctions

Abstract: The barrier system of the skin not only defends against antigens and harmful substances, but also hinders the permeation of medicines and cosmetics into the dermis. Several strategies have been developed to enhance the absorption ability of skin, including the use of chemicals and skin ablation devices. However, the cost and inconvenience of these strategies highlights the need for a novel and safe method for increasing skin absorption. In this study, we examined the effect of low temperature atmospheric press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…In our previous report, we reported that the NTP treatment on skin increased the absorption rate of external EGF through the skin33. Considering this transdermal drug delivery promoting property of NTP, we suggest that the pre-treatment of skin with NTP before the application of HC might bring grater curative results.…”
Section: Discussionmentioning
confidence: 77%
“…In our previous report, we reported that the NTP treatment on skin increased the absorption rate of external EGF through the skin33. Considering this transdermal drug delivery promoting property of NTP, we suggest that the pre-treatment of skin with NTP before the application of HC might bring grater curative results.…”
Section: Discussionmentioning
confidence: 77%
“…We previously reported that NTP treatment of keratinocytes caused the translocation of E-cadherin from cell border regions to the cytosol 27 . This suggested the possibility that keratinocytes could escape from the contact inhibition of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite many reports, the mechanism underlying NTP-mediated regeneration of skin tissue is not fully understood. We previously reported that NTP treatment modulated skin barrier function by inhibiting E-cadherin-mediated cellular interactions 27 . Given that E-cadherin is important for the formation of the skin barrier system and the regulation of keratinocyte proliferation, it has been suggested that NTP treatment might free keratinocytes from E-cadherin-mediated growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…LTAPP not only stimulates wound healing and skin surface decontamination [29, 30], but has also been suggested to be used for the cancer treatments [31, 32]. Furthermore, our previous study and the findings of Lademann et al, highlighted the safe and efficient transdermal drug delivery using LTAPP [33, 34]. Unlike other physical drug delivery systems, LTAPP can enhance drug absorption by temporary scattering cell-to-cell bonding in the epidermis, without harming tissues.…”
Section: Introductionmentioning
confidence: 89%
“…The Vapp of the plasma-treating mode is about 3 kV, and 2 slm (standard litters per minutes) of pure argon gas was used as a vehicle gas. Unlike the device in our previous reports [34], this new device produces the plasma glow only within plasma producing aisle, so that the plasma can’t contact to the skin directly. However, the device helped transdermal drug delivery activity effectively (Data not shown).…”
Section: Methodsmentioning
confidence: 99%